ANGIOGRAPHIC PATTERNS AND CLINICAL OUTCOMES OF IN-STENT RESTENOSIS IN DIABETIC PATIENTS FOLLOWING PERCUTANEOUS CORONARY INTERVENTION: A RETROSPECTIVE ANALYSIS - DURRANI , T; QADEER , A; HUSSAIN , I; KHAN , KM; SETHI , P; DURRANI , H (Biological and Clinical Sciences Research Journal, 2024)
In-stent restenosis (ISR) remains a significant complication after percutaneous coronary intervention (PCI), particularly in diabetic patients. Introducing drug-eluting stents (DES) has substantially reduced restenosis rates compared to bare-metal stents (BMS), yet diabetic patients continue to exhibit higher ISR rates due to their distinct vascular biology. Understanding the angiographic patterns and associated clinical outcomes of ISR in this population is crucial for optimizing treatment strategies. Objective: This study aims to evaluate the angiographic patterns of ISR in diabetic patients and compare the clinical outcomes of these patients to non-diabetic controls following PCI. Methods: A retrospective analysis was conducted on 1,452 patients who underwent coronary stenting and subsequent repeat angiography at a tertiary care centre between January 2021 and December 2023. The study population included 726 diabetic patients and 726 non-diabetic controls. Based on angiographic findings, ISR patterns were classified as focal, diffuse, proliferative, or occlusive. Clinical outcomes, including procedural success of repeat interventions and major adverse cardiovascular events (MACE) within 12 months, were compared between the two groups. Data were analysed using multivariate logistic regression to identify predictors of diffuse ISR patterns. Results: Diabetic patients exhibited significantly higher rates of diffuse ISR (46.3%) compared to nondiabetic patients (34.5%) (p<0.001). Focal ISR was more prevalent in non-diabetics (40.5% vs. 31.1%, p<0.001). Diabetic patients also had a higher incidence of MACE within 12 months (23.4% vs. 15.2%, p<0.001), with myocardial infarction being the most frequent event. Conclusion: Diffuse ISR is more common in diabetic patients and is associated with worse clinical outcomes compared to non-diabetic patients. These findings underscore the need for tailored interventions and close follow-up in diabetic patients post-PCI.